Co-creation in living labs - Hagy, S.; Morrison, Greg; Elfstrand, P. (2016)
© Springer International Publishing Switzerland 2017.Living Labs are places for open innovation where co-creation is a method for addressing real-life issues through the attribution of knowledge from science and society, the latter being a form of transdisciplinary social learning. In a Living Lab the representatives from business, society and academia, as well as citizens, have different value perceptions and propositions, providing heterogeneity across the stakeholder value spectrum. This provides a rich set of ideas and values for co-creation which can be used for both the operational phase and the integral shaping and creating the design for the physical infrastructure of the Living Lab itself. The use of co-creation workshops are demonstrated for ideation amongst the stakeholders for the HSB Living Lab. This is exemplified in the development of the social washing room which will be prototyped and tested in a fit-for-purpose multifunctional design space.